Handbook of research on emergent applications of optimization algorithms - Vasant, Pandian 1961-; Alparslan-Gök, S. Zeynep 1980-; Weber, Gerhard-Wilhelm 1960- (Advances in business information systems and analytics (ABISA) book series, 2018)
"This book explores the common practical and methodological interest for representatives of engineering and economics and provides a resource that will enable scientists and practitioners to quickly access the key notions of their domains using suitable methods and references to advance ahead and to branch further on the way to handle their institutions' problems and challenges"--